Clinical factors associated with calcific aortic valve disease. Cardiovascular Health Study. - Stewart, B F; Siscovick, D; Lind, B K; Gardin, J M; Gottdiener, J S; Smith, V E; Kitzman, D W; Otto, C M (J Am Coll Cardiol, 1997)
OBJECTIVES: The aim of this study was to determine the prevalence of aortic sclerosis and stenosis in the elderly and to identify clinical factors associated with degenerative aortic valve disease. BACKGROUND: Several lines of evidence suggest that degenerative aortic valve disease is not an inevitable consequence of aging and may be associated with specific clinical factors. METHODS: In 5,201 subjects > or = 65 years of age enrolled in the Cardiovascular Health Study, the relation between aortic sclerosis or stenosis identified on echocardiography and clinical risk factors for atherosclerosis was evaluated by using stepwise logistic regression analysis. RESULTS: Aortic valve sclerosis was present in 26% and aortic valve stenosis in 2% of the entire study cohort; in subjects > or = 75 years of age, sclerosis was present in 37% and stenosis in 2.6%. Independent clinical factors associated with degenerative aortic valve disease included age (twofold increased risk for each 10-year increase in age), male gender (twofold excess risk), present smoking (35% increase in risk) and a history of hypertension (20% increase in risk). Other significant factors included height and high lipoprotein(a) and low density lipoprotein cholesterol levels. CONCLUSIONS: Clinical factors associated with aortic sclerosis and stenosis can be identified and are similar to risk factors for atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Calcinosis; Female; Heart Valve Diseases; Humans; Male; Prospective Studies; Risk Factors; Sclerosis

Left ventricular diastolic filling in the elderly: the cardiovascular health study. - Gardin, J M; Arnold, A M; Bild, D E; Smith, V E; Lima, J A; Klopfenstein, H S; Kitzman, D W (Am J Cardiol, 1998)
Changes in left ventricular (LV) diastolic function (e.g., as measured by transmitral flow velocity) are known to occur with aging. In addition, impaired LV diastolic function plays an important role in such cardiovascular disorders common in the elderly as hypertension, ischemic heart disease, and congestive heart failure (CHF). Participants in the Cardiovascular Health Study, a multicenter study of community-dwelling men (n=2,239) and women (n=2,962) > or = 65 years of age, underwent an extensive baseline evaluation, including echocardiography. Early diastolic LV Doppler (transmitral) peak filling velocity decreased, and peak late diastolic (atrial) velocity increased with age in multivariate analyses (all p <0.001). Early and late diastolic peak filling velocities were both significantly higher in women than in men, even after adjustment for body surface area (or height and weight). In multivariate models in the entire cohort and a healthy subgroup (n=703), gender, age, heart rate, and blood pressure (BP) were most strongly related to early and late diastolic transmitral peak velocities. Early and late diastolic peak velocities both increased with increases in systolic BP and decreased with increases in diastolic BP (p <0.001). Doppler transmitral velocities were compared among health status subgroups. In multiple regression models adjusted for other covariates, and in analysis of variance models examining differences across subgroups adjusted only for age, the subgroup with CHF had the highest early diastolic peak velocities. All clinical disease subgroups had higher late diastolic peak velocities than the healthy subgroup, with the subgroups with either CHF or hypertension having the highest age-adjusted means. The subgroup with hypertension had the lowest ratio of early-to-late diastolic peak velocity, and men with CHF had the highest ratio. These findings are consistent with previous reports that hypertensive subjects exhibit an abnormal relaxation pattern, whereas patients with CHF develop a pattern suggestive of an increased early diastolic left atrial-LV pressure gradient.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Blood Flow Velocity; Cardiovascular Diseases; Cohort Studies; Diastole; Echocardiography, Doppler; Electrocardiography; Female; Health Status; Heart Ventricles; Humans; Male; Ventricular Function, Left

Association of aortic-valve sclerosis with cardiovascular mortality and morbidity in the elderly. - Otto, C M; Lind, B K; Kitzman, D W; Gersh, B J; Siscovick, D S (N Engl J Med, 1999)
BACKGROUND: Although aortic-valve stenosis is clearly associated with adverse cardiovascular outcomes, it is unclear whether valve sclerosis increases the risk of cardiovascular events. METHODS: We assessed echocardiograms obtained at base line from 5621 men and women 65 years of age or older who were enrolled in a population-based prospective study. On echocardiography, the aortic valve was normal in 70 percent (3919 subjects), sclerotic without outflow obstruction in 29 percent (1610), and stenotic in 2 percent (92). The subjects were followed for a mean of 5.0 years to assess the risk of death from any cause and of death from cardiovascular causes. Cardiovascular morbidity was defined as new episodes of myocardial infarction, angina pectoris, congestive heart failure, or stroke. RESULTS: There was a stepwise increase in deaths from any cause (P for trend, <0.001) and deaths from cardiovascular causes (P for trend, <0.001) with increasing aortic-valve abnormality; the respective rates were 14.9 and 6.1 percent in the group with normal aortic valves, 21.9 and 10.1 percent in the group with aortic sclerosis, and 41.3 and 19.6 percent in the group with aortic stenosis. The relative risk of death from cardiovascular causes among subjects without coronary heart disease at base line was 1.66 (95 percent confidence interval, 1.23 to 2.23) for those with sclerotic valves as compared with those with normal valves, after adjustment for age and sex. The relative risk remained elevated after further adjustment for clinical factors associated with sclerosis (relative risk, 1.52; 95 percent confidence interval, 1.12 to 2.05). The relative risk of myocardial infarction was 1.40 (95 percent confidence interval, 1.07 to 1.83) among subjects with aortic sclerosis, as compared with those with normal aortic valves. CONCLUSIONS: Aortic sclerosis is common in the elderly and is associated with an increase of approximately 50 percent in the risk of death from cardiovascular causes and the risk of myocardial infarction, even in the absence of hemodynamically significant obstruction of left ventricular outflow.
Keywords: Aged; Angina Pectoris; Aortic Valve; Calcinosis; Cardiovascular Diseases; Cerebrovascular Disorders; Female; Heart Failure; Heart Valve Diseases; Humans; Male; Mortality; Myocardial Infarction; Prospective Studies; Risk; Risk Factors; Ultrasonography; United States; Ventricular Outflow Obstruction

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Importance of heart failure with preserved systolic function in patients > or = 65 years of age. CHS Research Group. Cardiovascular Health Study. - Kitzman, D W; Gardin, J M; Gottdiener, J S; Arnold, A; Boineau, R; Aurigemma, G; Marino, E K; Lyles, M; Cushman, M; Enright, P L (Am J Cardiol, 2001)
Although congestive heart failure (CHF) is a common syndrome among the elderly, there is a relative paucity of population-based data, particularly regarding CHF with normal systolic left ventricular function. A total of 4,842 independent living, community-dwelling subjects aged 66 to 103 years received questionnaires on medical history, family history, personal habits, physical activity, and socioeconomic status, confirmation of pre-existing cardiovascular and cerebrovascular disease, anthropometric measurements, casual seated random-zero blood pressure, forced vital capacity and expiratory volume in 1 second, 12-lead supine electrocardiogram, fasting glucose, creatinine, plasma lipids, carotid artery wall thickness by ultrasonography, and echocardiography-Doppler examinations. Participants with at least 1 confirmed episode of CHF by Cardiovascular Health Study criteria were considered prevalent for CHF. The prevalence of CHF was 8.8% and was associated with increased age, particularly for women, in whom it increased more than twofold from age 65 to 69 years (6.6%) to age > or = 85 years (14%). In multivariate analysis, subjects with CHF were more likely to be older (odds ratio [OR] 1.2 for 5-year difference, men OR 1.1), and more often had a history of myocardial infarction (OR 7.3), atrial fibrillation (OR 3.0), diabetes mellitus (OR 2.1), renal dysfunction (OR 2.0 for creatinine < or = 1.5 mg/ dl), and chronic pulmonary disease (OR 1.8; women only). The echocardiographic correlates of CHF were increased left atrial and ventricular dimensions. Importantly, 55% of subjects with CHF had normal left ventricular systolic function and 80% had either normal or only mildly reduced systolic function. Among subjects with CHF, women had normal systolic function more frequently than men (67% vs 42%; p < 0.001). Thus, CHF is common among community-dwelling elderly. It increases with age and is usually associated with normal systolic LV function, particularly among women. The finding that a large proportion of elderly with CHF have preserved LV systolic function is important because there is a paucity of data to guide management in this dominant subset.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Echocardiography, Doppler; Female; Health Status; Heart Failure; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Surveys and Questionnaires; United States; Ventricular Function, Left